Assessment: Problem and Solution at the Joho Village Convection Center, Sleman, Special Region of Yogyakarta - Anas Hidayat; Nur Ellyanawati Esty Rahayu; Mellisa Fitri Andriyani Muzakir; Dian Retnaningdiah; Muafi; Prakarsa Panjinegara; Farah Aida Ahmad Nadzri (Asian Journal of Community Services, 2023)
The purpose of this activity is to conduct an assessment by identifying and providing solutions to the border industry in Joho, Condong Catur, Yogyakarta. The methods employed in this community service program were observation, interviews, and Focus Group Discussion (FGD). The result obtained was the formation of a need assessment pattern to increase business capacity through organizational improvement, improvement of job competencies, and individual competencies. Education, training, and mentoring are required for an increased organization to create a strategy and corporate values. Providing education, training, and mentoring is a business management requirement to increase work competence and individual competence by improving product quality and creative and innovative human resources.